A comparison of methanogens of different regions of the equine hindgut - Murru, Francesca; Fliegerova, Katerina; Mura, Erica; Mrázek, Jakub; Kopečný, Jan; Moniello, Giuseppe (Anaerobe, 2018)
The diversity of the methanogenic archaea associated with the six segments of the horse and donkey hindgut (caecum, right ventral colon, left ventral colon, left dorsal colon, right dorsal colon, and rectum) was analyzed using 16S rDNA gene clone library. A total of 641 positive clones, 321 from the horse and 320 from the donkey hindgut, were examined by the RFLP, revealing 9 different ribotypes, 8 in the horse and 5 in the donkey hindgut. In both the animals Methanobacteriales (Methanobrevibacter-like sequences) and Methanomicrobiales (Methanocorpusculum-like sequences) were detected as the dominant orders followed by the uncultured Methanomassiliicoccales. The composition of the equine archaeal community was found to be dependent on the gut region. In both the two animals no Methanobrevibacter-like clones were detected in the caeca, which were instead inhabited by the Methanocorpusculum-like archeons. The Methanosarcinales were found only in distal regions of the horse hindgut.
Keywords: Animals; biodiverzita; ribozomální DNA; DNA, Ribosomal; DNA archebakterií; Donkey; Ribotype; koně; Horses; Archaea; Phylogeny; methan; Horse; Biodiversity; Equidae; DNA, Archaeal; Methanogens; Methane; Hindgut; tlusté střevo; zvířata; fylogeneze; Intestine, Large